2011
DOI: 10.1007/s10439-011-0273-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Combined Cyclic Stretch and Pressure on the Aortic Valve Interstitial Cell Phenotype

Abstract: Aortic valve interstitial cells (VIC) can exhibit phenotypic characteristics of fibroblasts, myofibroblasts, and smooth muscle cells. Others have proposed that valve cells become activated and exhibit myofibroblast or fibroblast characteristics during disease initiation and progression; however, the cues that modulate this phenotypic change remain unclear. We hypothesize that the mechanical forces experienced by the valve play a role in regulating the native phenotype of the valve and that altered mechanical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 30 publications
3
44
0
Order By: Relevance
“…Others have also identified stretch as being a modulator of myofibroblast phenotype (Thayer et al, 2011). Additional factors have been shown to affect myofibroblast phenotype, for example, Wnt3a signaling (Carthy et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Others have also identified stretch as being a modulator of myofibroblast phenotype (Thayer et al, 2011). Additional factors have been shown to affect myofibroblast phenotype, for example, Wnt3a signaling (Carthy et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…44,45,106,108 These findings have potentially provocative implications linking pathological stretch with the deterioration in aortic valve tissue properties and function that occurs with disease. Indeed, Thayer et al 45 found that subjecting aortic valve leaflets to a combination of pathological stretch and pressure loads ex vivo caused a significant increase in the thickness of the fibrosa and spongiosa layers ( Figure 4C). …”
Section: Hemodynamic Effects On Aortic Vicsmentioning
confidence: 99%
“…VIC phenotype and function are regulated by cues from their local environment, including paracrine signaling molecules (eg, endothelium-derived signals as discussed below), inflammatory cytokines (eg, TGF-β1), 19 the biochemical and biomechanical properties of their ECM, 11,22,23,[36][37][38][39][40] and mechanical stimuli induced by hemodynamic forces (eg, normal or pathological stretching of the valve tissue). [41][42][43][44][45] In addition, there appear to be interactions, and sometimes synergies, between each of these types of cues, with the mechanical environment playing a critical modulatory role. For example, increases in the transvalvular pressure gradient (TPG) lead to higher levels of valve tissue stretching, 46 likely resulting in mechanical activation of latent TGF-β1, 20 which in turn can potentiate VIC activation to the myofibroblast phenotype.…”
Section: Aortic Valve Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This well‐accepted role of flow is a conceptual extension from vascular endothelial cells (ECs) to VEC: Flow shear forces affect the biology of both VEC and vascular ECs with many similarities and some differences 16, 17, 18. However, other forces acting on leaflets also clearly influence valve cellular biology 19. Elevated transvalvular pressure (eg, in the setting of hypertension) is a recognized risk factor for commissural fusion during VAD therapy as well as valvular diseases presumably attributed to the increased static pressure on valve cells and the increased strain loading on the closed AV root 13, 20.…”
Section: Discussionmentioning
confidence: 99%